A Comparative Study of Dentoskeletal Changes Following Orthodontic Treatment with First Premolar Extraction in Long Face and Normal Patients - Farzin Heravi; Shiva Shojaeian; Mehdi Sadafi (Mashhad University of Medical Sciences, 2013)
Introduction: The purpose of this study was to evaluate vertical facial and dental changes after orthodontic treatment with extraction of first four premolars, and to find whether long facial height could influence the treatment result. Methods: Fifty-six orthodontic patients with the minimum age of 15, whose treatment plan involved extracting four first premolars, participated in the study. The patients included 30 females and 27 males. Cephalometric measurements before and after treatment were compared using a paired T-test. Independent T-test was employed to compare post treatment changes for each parameter between normal and long face groups. The same analysis performed between male and female subjects. Results: Treatment changes revealed a significant increase in the vertical distance from the upper molar to palatal plane, the lower molar to mandibular plane and Menton to palatal plane in all groups. There was significantly more increase in most post-treatment linear measurements in males than in females, with the same direction in both genders. There were no significant differences between normal and long face in any measurement. Conclusion: All patients showed some extrusion of the molar teeth after extraction of the premolars. The difference between normal and long face groups was not significant.